2015
DOI: 10.1074/jbc.m115.647008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Autoantibodies against Complement Component C3 in Patients with Lupus Nephritis

Abstract: Background: Autoantibodies against complement C3 are found in patients with the autoimmune disease systemic lupus erythematosus. Results: C3 autoantibodies are found in 30% of lupus nephritis patients and inhibit C3 interaction with the regulatory proteins Factor H and CR1. Conclusion: C3 autoantibodies have overt capability to overactivate complement. Significance: C3 autoantibodies can contribute to the pathological process in lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 48 publications
2
68
3
Order By: Relevance
“…Therefore, further studies are needed in order to clarify if anti-FB and anti-C3b autoantibodies have a primary mechanistic role in the pathology of the lipodystrophy or if they rather secondarily arise as a consequence of the increase in circulating complement proteins produced due to unabated complement activation in the presence of C3NeF. A plausible possibility in line with the presence of C3NeF and low C3 levels in our BSS cohort is that these autoantibodies synergistically promote further C3 convertase stabilization and C3 consumption in serum, similarly to what has already been described by Vasilev and colleagues for anti-C3 and anti-C3b autoantibodies in patients with lupus nephritis [33,34].…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, further studies are needed in order to clarify if anti-FB and anti-C3b autoantibodies have a primary mechanistic role in the pathology of the lipodystrophy or if they rather secondarily arise as a consequence of the increase in circulating complement proteins produced due to unabated complement activation in the presence of C3NeF. A plausible possibility in line with the presence of C3NeF and low C3 levels in our BSS cohort is that these autoantibodies synergistically promote further C3 convertase stabilization and C3 consumption in serum, similarly to what has already been described by Vasilev and colleagues for anti-C3 and anti-C3b autoantibodies in patients with lupus nephritis [33,34].…”
Section: Discussionsupporting
confidence: 79%
“…The low C3 and C4 levels may result in a vicious cycle, because, in turn, accumulated IC activates and consumes complement through classical pathway [26]. Besides, autoantibodies such as anti-C1q could damage complement [27], and it has recently been reported that anti-C3 autoantibody levels correlated with disease activity [28]. Most SLE patients are complement deficient, and their immune system cannot clear IC effectively, increasing IC deposits to cause damage to organs or systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the serum samples positive for anti-C3 antibodies, the levels of C3 were significantly lower, compared with the negative samples. The authors speculate that anti-C3 antibodies enhance C3 convertase, resulting in a more efficient C3 cleavage [126]. In another study, antibodies against C3b, although less frequent than that against C1q, showed a higher specificity for LN, particularly for the prediction of renal flare [127].…”
Section: Lupus Nephritismentioning
confidence: 97%
“…To date, the autoantibodies against C3 and C3b have been reported in LN (Table 2) [126,127]. In the Bulgarian population, anti-C3 antibodies were present in 31% of patients (in 12 of total 39 individuals), and they correlated positively with anti-dsDNA antibodies levels, as well as with the severity of LN.…”
Section: Lupus Nephritismentioning
confidence: 99%